2021
DOI: 10.1111/iej.13650
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of research methods and experimental models to study removal of root filling materials

Abstract: Despite enjoying high favourable outcome rates, root canal treatment is not always successful. Root canal retreatment is a widely practised option for managing a nonhealing root treated tooth. A basic distinction between retreatment and initial treatment is the requirement to remove the existing root filling material occupying the Nguyen et al. (2019) Crozeta et al. (2020) Prati et al. (2020) Crozeta et al. (2021) Clearing and splitting Fariniuk et al. (2017) MCT and CLM Canali et al. (2019) Others Binary (Yes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 303 publications
(405 reference statements)
0
3
0
Order By: Relevance
“…The remaining root canal filling material can be analyzed by sectioning and assessment under a scanning electron microscope (SEM) or stereomicroscope [10,11,20]. These techniques may result in the loss of material and influence the result [21]. Moreover, they only allow the analysis of the surface area covered, not the volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining root canal filling material can be analyzed by sectioning and assessment under a scanning electron microscope (SEM) or stereomicroscope [10,11,20]. These techniques may result in the loss of material and influence the result [21]. Moreover, they only allow the analysis of the surface area covered, not the volume.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they only allow the analysis of the surface area covered, not the volume. These drawbacks can be overcome by the use of non-invasive, three-dimensional imaging techniques (CBCT, microcomputed tomography) [9,13] and weight assessment [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several solvents have been proposed to soften the obturation materials, such as chloroform, eucalyptus oil, xylene/xylol, methyl chloroform, tetrahydrofuran, methylene chloride, halothane or rectified turpentine. 77 However, some concerns have been raised regarding their cytotoxicity and the amount of filling material remnants in root canals. Horvath et al demonstrated that the use of solvent in RCRts resulted in more gutta-percha and sealer remnants on root canal walls and inside dentinal tubules that could potentially compromise the following chemo-mechanical disinfection and obturation procedures, jeopardizing the RCRts outcome.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…Due to the enhanced mechanical and metallurgical properties of NiTi instruments in comparison to stainless-steel manual files, the removal of previous root filling materials is more effective, and efficient, and requires less operative time, resulting in fewer remnants in the root canal system. 76 , 77 Despite this, the main risks of using NiTi instrument for the removal of filling materials are the instrument fracture and iatrogenic errors such as ledge, stripping, false channel formation, and perforation, especially with the retreatment instrument with an active tip. Two other additional techniques have been proposed for root filling materials removal, the ultrasonic devices and lasers.…”
Section: Clinical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation